Epidemiology of JapaneseâBâ encephalitis infection in pigs in Riau and North Sumatera Provinces - Sendow, Indrawati; Syafriati, Tatty; Hadi, Upik Kesumawati; Malole, Martin; Soviana, Susi; ., Darminto (Indonesian Animal Sciences Society, 2003)
Epidemiology study on Japanese-B-Encephalitis (JE) was conducted in Riau and North Sumatera Provinces. A total of 190 pig sera from Riau Province and 164 pig sera from North Sumatera were tested using competitive ELISA (C-ELISA) to detect antibodies against JE virus. Insect collection was also conducted using several methods near pig farms in those provinces and identified into species to gain more information on its role to distribute JE infection. Serological results indicated that 70% pig in Sumatera and 94% pig in Riau had antibodies against JE virus. The highest prevalence of reaktor was detected in pig of more than 4 months age in both Provinces. The results of insect collection showed that Culex tritaeniorchynchus and Culex quinquefasciatus were the most dominant species in both provinces. Based on serological testing, indicated that JE virus infected pig in Sumatera and Riau Provinces, and higher reactor was obtained in older pig. Culex tritaeniorchynchus and Culex quinquefasciatus were the dominant insect species in both provinces, hence those species had a possibility to play an important role of JE transmission. Â Key words: JE, pigs, serology, insects